Eosinophilic duodenitis associated to food allergy debuting as acute visceral pain in an adult with vitiligo: a case report - Bornacelly Mendoza, Adriana Paola (2023)
Background: Eosinophilic duodenitis has a prevalence of 5.1 to 8.2 per 100000 persons. The underlying molecular mechanisms are unknown, but hypersensitivity (seasonal and food allergies, asthma, eczema) response plays a major role in its pathogenesis, allergic predisposition can be found up-to 25-35% of cases. The diagnosis includes clinical manifestation, imaging findings and histological evidence of eosinophilic infiltration >20 eosinophils per high-power field. This is a clinical case report. a 25-years old man with vitiligo consult to emergency department referring dyspepsia symptoms, vomiting and abdominal pain of maximal intensity, in the medical exam upper abdominal pain was found, blood laboratories were unremarkable except a high net eosinophil-count >2000 cells/ul, abdominal ultrasound were normal, upper endoscopy revealed duodenitis with rigid and thickened folds, colonoscopy show hemorrhoids grade I. Coproscopy exam was negative for parasites, total IgE, IgA and IgG were in normal range, a positive IgG to Toxoplasma gondii was reported, autoimmunity panel was negative. In the following 4 days the abdominal pain and eosinophils count increase, a new abdomin-pelvic tomography was done showing thickened duodenum with a new endoscopy showing marked edema in duodenum with severe biliary reflux with biopsies describing an atrophic chronic duodenitis. Allergy tests -skin prick and patch tests- were done resulting positive to cereals (rye, soy, barley), Manihot esculenta, green banana, tomato, cow milk, orange and pineapple. A restrictive diet and protons pump inhibitor was indicated, ambulatory control at 45 days after show symptoms resolution with a normal blood eosinophils count. Here is reported a case of eosinophilic duodenitis related to food allergy in a young man with vitiligo debuting with an unusual clinical presentation of acute visceral pain and biliary reflux which resolved with elimination diet and panto oids, with both, IgE and non-IgE mechanisms playing important roles explaining food sensitization.